Research Priorities to Improve Future Environmental Water Outcomes - Horne, Avril C.; Webb, J. Angus; O'Donnell, Erin; Arthington, Angela H.; McClain, Michael; Bond, Nicholas; Acreman, Mike; Hart, Barry; Stewardson, Michael J.; Richter, Brian; Poff, N. LeRoy (Frontiers in Environmental Science, 2017)
Significant progress in environmental flow management has occurred in recent years due to several factors. These include governments committing to environmental flow programs, significant progress in scientific understanding, and environmental flow assessment methods that are cognizant of stakeholder participation and co-design. However, there remain key challenges facing environmental water management. In this paper, we report on a horizon scanning exercise that identified the questions, which, if answered, would deliver much needed progress in the field of environmental water management. We distributed an online survey to ask researchers and practitioners in the field of environmental water management to identify the key questions. The authors then consolidated 268 submitted questions and organized them into key themes. The consolidated list was presented to a workshop of environmental water researchers and practitioners, where attendees were asked to review the questions, vote on the most important, and provide feedback on gaps, issues, or overlaps. The breadth of issues facing environmental water management is captured by the six key themes into which questions were classified: (1) Ecological knowledge and environmental flow assessment methods, (2) Adaptive management, (3) Integrated management and river objectives, (4) Knowledge transfer: applying best practice in a global context, (5) Community knowledge and engagement, and (6) Active management. These questions provide a roadmap for research and management innovations that will improve the effectiveness of environmental flows programs.